School nurses on the 'other' front line. (2nd August 2021) - White, Sharon
Abstract : Sharon White discusses the recent changes to school nursing services to reflect the need for stronger risk management processes and an awareness of vulnerable groups of children and young people, as well as her admiration of school nurses as she shares personal anecdotes of the impact she has seen school nurses make to the lives of children, young people and their families